1992
DOI: 10.1038/360765a0
|View full text |Cite
|
Sign up to set email alerts
|

Pit-1-dependent expression of the receptor for growth hormone releasing factor mediates pituitary cell growth

Abstract: In Snell (dw) and Jackson (dwJ) dwarf mice, mutations in the gene encoding Pit-1, a tissue-specific POU-domain transcription factor, lead to the absence of somatotroph, lactotroph and thyrotroph cells. Pre-somatotroph proliferation is stimulated by increased intracellular levels of cyclic AMP, normally induced by growth hormone releasing factor (GRF; refs 7-17). Here we report the cloning of mouse and rat complementary DNAs encoding a new member of the seven-transmembrane-helix, G-protein-coupled receptor fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
167
0
2

Year Published

1995
1995
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(174 citation statements)
references
References 33 publications
5
167
0
2
Order By: Relevance
“…Recent studies have provided information on the molecular basis of the specific regulation of PRL and GH gene transcription that could play an important role in the process of transdifferentiation. It was suggested that Pit-1 expression may directly or indirectly regulate somatotrophs and lactotrophs through activation of GRH and somatostatin receptors on the one hand and of dopamine on the other hand (35)(36)(37). In addition to Pit-1, other transcription factors and homeobox genes may be required for generating various pituitary cell phenotypes belonging to the Pit-1 lineage (38 -40).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided information on the molecular basis of the specific regulation of PRL and GH gene transcription that could play an important role in the process of transdifferentiation. It was suggested that Pit-1 expression may directly or indirectly regulate somatotrophs and lactotrophs through activation of GRH and somatostatin receptors on the one hand and of dopamine on the other hand (35)(36)(37). In addition to Pit-1, other transcription factors and homeobox genes may be required for generating various pituitary cell phenotypes belonging to the Pit-1 lineage (38 -40).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the clusters specify position along axes in an embryo and limbs (1). Besides these clustered homeobox genes, certain of the unclustered and more divergent homeobox genes have been assigned roles in growth control, organogenesis, or establishment of cellular phenotypes (2)(3)(4)(5). Indeed, one of the unclustered homeobox gene, HOX11 (6)(7)(8)(9), controls the genesis of spleen (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In almost all cases they have important roles in cellular differentiation and exhibit a characteristic ability of recognizing diverse DNA elements. Pit-1, for instance, is expressed exclusively in the anterior pituitary gland and is responsible for both the development of three of the five endocrine cell types and the tr^iis-activation of several genes, including prolactin (Prl) and growth hormone (GH) genes (Bodner et al 1988;Ingraham et al 1988;Li et al 1990;Lin et al 1992). Pit-1 binds to a complex pattern of sites within the promoters and enhancers of the genes it regulates.…”
mentioning
confidence: 99%